INDIKATOR-INDIKATOR KONSUMEN DALAM MEMILIH COFFEE SHOP (STUDI KASUS: KONSUMEN COFFEE SHOP PROVINSI ACEH) - Dedy Darmansyah (Jurnal Bisnis Tani, 2019)
The potential of a coffee shop is very high where demand is increasing every year. Coffee shop entrepreneurs must know what are the main indicators of consumers in choosing a coffee shop so that they are able to meet consumer demand well. This research was conducted in Aceh Province in February 2019 - April 2019 using primary data and secondary data through observation, questionnaire distribution, literature study and documentation study. The observations produced eleven indicators that were considered by consumers in the province of Aceh in choosing a coffee shop namely delicious coffee taste, good service, a comfortable place, a variety of processed coffee drinks, affordable prices, food choices as an additional menu, facilities provided by coffee shop, recommendations from friends, the location of the nearest coffee shop, get to know coffee shop owners and famous coffee shop brands. The results of this study indicate that the most important indicator for consumers in choosing a coffee shop is a delicious coffee flavor with a percentage of 20 percent for male consumers and 21 percent for female consumers.